Cost-effectiveness of switching from tenofovir disoproxil fumarate to tenofovir alafenamide versus entecavir for chronic hepatitis B patients in Greece - Emmanouil Sinakos; Nandita Kachru; Christos Tsoulas; Sushanth Jeyakumar; Nathaniel J Smith; Alon Yehoshua; Evangelos Cholongitas (Becaris Publishing Limited, 2024)
Aim: This study assessed the clinical impact and cost-effectiveness of switching from tenofovir disoproxil fumarate (TDF) to either tenofovir alafenamide (TAF) or entecavir (ETV) in a Greek chronic hepatitis B (CHB) population. Patients & methods: A Markov model from the perspective of a third-party payer in Greece quantified the health and economic benefits of switching from TDF to either TAF or ETV over a lifetime horizon. Results: Over a lifetime, patients who switch from TDF to TAF versus patients who switch from TDF to ETV had an overall lower incidence of compensated cirrhosis (0.4% lower), decompensated cirrhosis (0.04% lower) and hepatocellular carcinoma (0.25% lower). Chronic kidney disease and endstage renal disease were also lower in patients who switch to TAF; major osteoporotic fractures were similar for both groups. While total costs were higher for switching from TDF to TAF versus TDF to ETV due to the higher cost of TAF, switching from TDF to TAF versus ETV was cost effective with an incremental cost-effectiveness ratio of €17,113 per quality-adjusted life year. Conclusion: Switching from TDF to TAF in patients living with CHB is a cost effective strategy to reduce adverse liver disease outcomes, while improving bone- and renal-related safety outcomes.